Effects of TENS on Pain, Disabiliy, Quality of Life and Depression in Patients with Knee Osteoarthritis - Fırat Altay,; Dilek Durmuş,; Ferhan Cantürk, (Archives of Rheumatology, 2010)
Objective: The aim of this randomized controlled trial was to evaluate the effects of transcutaneous electrical nerve stimulation (TENS) on pain, disability, functional performance, quality of life (QoL) and depression in patients with knee osteoarthritis (OA). Materials and Methods: Forty patients with primary knee OA diagnosed according to The American College of Rheumatology criteria were randomized into groups. Patients in the Group 1 received TENS, exercise program and hot pack. Group 2 received placebo TENS, exercise program, hot pack and served as a control group. Assessment of pain (visual analog scale, VAS; Western Ontario McMaster Osteoarthritis Index, WOMAC pain score), disability and stiffness (WOMAC physical function and stiffness score), functional performance (6-minute walk distance test, 6MWD; 10 steps stairs climbing up-down time), QOL (Short Form 36, SF 36) and depression (Beck Depression Inventory, BDI) were done in all patients before and after the treatment. Treatment sessions were performed 5 days a week, for 3 weeks. Results: Both groups showed significant improvements in pain, disability, stiffness, functional performance, most of the subscores of SF 36 and depression score after the 3 weeks treatment program. The improvements in pain, WOMAC pain, disability and sub-scores of SF 36 were better in the active TENS group compared to the control group. Conclusion: The results of this study suggest that addition of TENS to hotpack and exercise program is more effective in decreasing knee pain and related disability and improving QoL in patients with knee OA. (Turk J Rheumatol 2010; 25: 116-21)